Customers’ perceptions on ESKOM’s pre-paid billing system and the effects on their satisfaction and trust - Chinomona, R; Sandada, M (My University, 2014)
Despite the increasing awareness of the paramount importance of customer satisfaction and trust in the context of large firms, research efforts focused on the investigation of the role of electricity pre-paid system performance on customer satisfaction and trust have largely remained scant, particularly in developing countries of Southern Africa. Therefore, the primary objective of this study is to fill this void. Three research hypotheses are posited and a sample data of 151 collected from ESKOM company’ electricity pre-paid system customer is used to empirically test the hypotheses. The results of this study show that, the performance of the ESKOM prepaid billing system positively influences the customers’ satisfaction and trust in a significant way. Managerial implications of the findings are discussed and limitations and future research directions are indicated.
Keywords: Customer satisfaction; Customer trust; Pre-paid system